History of Slaves in Qatar: Social Reality and Contemporary Political Vision - Al-Mulla, Mariam Ibrahim (Journal of History Culture and Art Research, 2017)
Museums today play vital roles in the Arabian Peninsula in general and Qatar in particular. These functions vary between the social, economic and political. Recently, Qatar museums’ practices have focused on a political role. To highlight this role, I will take the recently opened slavery museum Bin Jelmood House (BJH) as a case study in this article. This paper aims to discuss and analyse the use of BJH in a comprehensive ‘soft power’ strategy to deflect international criticism of Qatar following the decision to award the 2022 World Cup to the country. Analysing BJH’s narrative was problematic, as the museum chooses to display a particular history which has been politicized to fit directly into Qatar’s international politics. The central questions this paper focuses on are as follows: Why was this specific social history chosen? What purpose does BJH serve? Why is Qatar trying to portray itself as liberating and open? To find the answers, I first interviewed the museum’s researchers, who talked about the process of collecting that specific narrative of the museum and the audience’s reaction. Second, analysing the museum’s narrative shows that museum practice today creates a different starting point than it used to, such as new ideas, strategies and policies. That conveyance the museum’s desire to become more open and liberal compared to previous practices.